2019
DOI: 10.1016/j.jaip.2018.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Plasma Polyunsaturated Fatty Acids Are Inversely Associated with Asthma and Atopy in Early Childhood

Abstract: PUFA dietary intake and plasma levels are inversely associated with asthma and/or recurrent wheeze and atopy at age 3 years. Antenatal vitamin D could modulate the effect of early childhood PUFA on risk of asthma and allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 55 publications
(139 reference statements)
4
49
2
Order By: Relevance
“…27 Indeed, dietary and circulating PUFAs have been associated with asthma, including in the VDAART cohort. 24 However, we found no association between plasma PUFAs and intestinal PUFAs in the present analysis. Although members of the human intestinal microbiota are not known to produce PUFAs, some participate in metabolism of PUFAs.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…27 Indeed, dietary and circulating PUFAs have been associated with asthma, including in the VDAART cohort. 24 However, we found no association between plasma PUFAs and intestinal PUFAs in the present analysis. Although members of the human intestinal microbiota are not known to produce PUFAs, some participate in metabolism of PUFAs.…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, we found that plasma PUFAs were inversely associated with asthma at age 3 years in VDAART participants. 24 Given the present findings of inverse associations between intestinal PUFAs and other lipid metabolite modules and asthma, we hypothesized that plasma and intestinal lipids can be correlated. However, we found no correlation between plasma PUFAs (total, omega-3 or omega-6), endocannabinoids, or diacylglycerols and their corresponding intestinal metabolite module eigenvalues (see Table E6 in this article's Online Repository at www.jacionline.org).…”
Section: Intestinal and Plasma Metabolomes Associate With Childhood Amentioning
confidence: 94%
“…The presence of caffeine was associated with lower odds of asthma at 3 years of age. Her group found that high concentrations of polyunsaturated fatty acid (PUFA) and Vitamin D were associated with a large reduction in asthma risk (52). They also identified a potential role in asthma of the sphingolipid biosynthesis regulator ORMDL3.…”
Section: Systems Biologymentioning
confidence: 99%
“…It was shown in mice that deficiency of dietary fiber intake increases the susceptibility to OVA induced allergic airway inflammation (121). Additionally, it was shown that uptake of polyunsaturated fatty acids can increase the production of SCFA's by bacteria (122) and the dietary intake of poly unsaturated fatty acids was inversely associated with atopy in childhood (123).…”
Section: Oral Tolerancementioning
confidence: 99%